Association between sex hormones and ambulatory blood pressure. Issue 11 (November 2018) - Jiménez, Monik C.; Wang, Lu; Buring, Julie E.; Manson, JoAnn E.; Forman, John P.; Sesso, Howard D.
Abstract : Introduction: Higher levels of total testosterone and lower levels of sex hormone-binding globulin (SHBG) have been associated with increased blood pressure (BP) in women with an inverse association between total testosterone and BP among men. Fewer studies have examined associations with 24-h ambulatory blood pressure (ABP), blunted nocturnal BP decline or the role of dehydroepiandrosterone sulfate (DHEAS), a precursor to androgens. Methods: Baseline blood samples were assayed for 229 normotensive men (≥50 years) and women (≥55 years) participating in the VITamin D and OmegA-3 TriaL. Standardized seated BP (SBP and DBP) and 24-h ABP were measured by trained technicians. Self-reported cardiovascular risk factors and sociodemographic variables were reported on baseline questionnaires. Sex stratified linear regression models adjusted for age, race/ethnicity, BMI, smoking and alcohol estimated the association between each sex hormone and measures of BP and 24-h ABP. Logistic regression used to estimate associations with blunted nocturnal decline (>10% reduction in SBP or DBP during sleeping hours). Results: Total testosterone and SHBG demonstrated significant inverse correlations with SBP whereas DHEAS was not significantly associated with BP. Among men, in multivariable analyses, each 10% increase in DHEAS was associated with a 0.41 mmHg higher seated DBP ( β  = 4.29, 95% CI 0.84−7.73) and each 10% increase in total testosterone and SHBG was associated with a 0.54 mmHg ( β  = −5.65, 95% CI −10.45 to −0.84) and 0.60 mmHg ( β  = −6.30, 95% CI −11.38 to −1.21) decrease in seated DBP, respectively. No significant associations were observed among women. Conclusion: Among men only, we observed statistically significant inverse cross-sectional associations between total testosterone and SHBG with seated DBP, and a significant positive association with DHEAS levels.